Trilateral Engagement in Nepalese Geopolitics: Soft Power Approach in Nepal's Foreign Policy - Chand, Hari Prakash (Nepal Public Policy Review, 2021)
The contemporary South Asian geopolitics in general and Nepalese geopolitics, in particular, is a crucial factor to analyze trilateral engagement, and their affairs in Nepal. Geopolitics is one of the major factors of shaping and reshaping bilateral and multilateral relations. It is influenced by the actions and reactions of geopolitical players. They sometimes push their actions broadly to achieve their national and global interests, and sometimes even narrow down their actions. But, whatever their actions, their national and global interests continue to grow. China, India and the USA have been dealing, in one way or the other, to widen, broaden and defend their national and regional interests. Dealing of three super and great powers in Nepal have dealt based on the changing geopolitics which greatly implicates Nepalese domestic affairs and foreign policy. This paper mainly assesses the engagement of the USA, China, and India in Nepal, and how their power play implicates Nepal's foreign policies. It aims to explore Nepal’s way of moving forward in the context of the Belt and Road Initiatives (BRI), Millennium Challenge Corporation (MCC), and the newly emerged China-Russia security dialogue platform. The paper adapts interpretivism as the philosophical position and hence method is qualitative. It only focuses on geopolitics, BRI, MCC, and China-Russia security dialogue platform. The conclusion of the paper is that Nepal’s foreign policy should be based on soft power discourse to eliminate the issues of any kind of regional and global security alliance with super and great powers.